Relationship of COVID-19 Anxiety With Depression, Stress, and Anxiety Among Administrative Staff and Nurses in a Referral Hospital for Corona - Rohollah Fallah Madvari; Mahdi Jafari Nodoushan; Reyhane Sefidkar; Ziba Loukzadeh; Fahimeh Teimouri; Mohammad Hassan Basirinezhad; Moein Nemati; Mohadeseh Bagheshahi (Shahrekord University of Medical Sciences, 2022)
Background and aims: The prevalence of the coronavirus disease 2019 (COVID-19) was associated with many psychological consequences among personnel of hospitals. The aim of this study was to investigate the relationship between COVID-19 anxiety and depression, stress, and anxiety among administrative staff and nurses. Methods: This is a cross-sectional study that was conducted in January 2022. All 100 nurses and administrative staff of a hospital participated in this study. Demographic information questionnaires, Corona Disease Anxiety Scale, and Depression Anxiety Stress Scale (DASS-21) were employed to collect data. Statistical analysis was performed using SPSS software version 24. Results: The mean ± standard deviation age of participants was 33.53 ± 6.73 years. The median (interquartile range) disease anxiety in nurses and administrative staff was equal to 7 (4.25) and 10 (8), respectively. Further, COVID-19 anxiety was significantly higher in administrative staff (P = 0.001); moreover, a significant relationship was found between the history of COVID-19 disease and disease anxiety (P = 0.04). Nurses reported higher stress than administrative staff (P = 0.02), and no significant relationship was found between COVID-19 anxiety and components of DASS (P > 0.05). Conclusion: In this study, COVID-19 anxiety was significantly higher in administrative staff. Therefore, during the COVID-19 pandemic, it is necessary to pay attention to all jobs. Nurses reported higher stress and depression. Therefore, it is suggested that the necessary psychological measures be taken to improve their psychological states. Increasing the number of nurses, improving working conditions, reducing workload, and training can be effective in improving the mental health of nurses.